Private Sector Voluntary Initiatives on Labor Standards - Newitt, Kirsten (World Bank, Washington, DC, 2013)
This paper considers the roles and functions of private sector initiatives that companies voluntarily adopt in order to uphold, monitor, and improve labor standards and working conditions in global supply chains through activities such as corporate codes of conduct, guidelines, recommendations, and rules. Over the past 20 years, an array of voluntary private sector initiatives has emerged to improve working conditions in global supply chains. Despite some positive impacts, they appear to be weaker with respect to rights-based and equity issues and most likely benefit permanent workers rather than vulnerable workers in temporary, seasonal, and home-based jobs. One of the most powerful tools for strengthening the impact of voluntary initiatives is to build the capacity of actors in developing countries—including employers, workers, and their representatives and government authorities—to act as agents of change, which would not only strengthen initiatives on labor standards, but potentially also maximize positive spill-over into broader processes of social and economic development. Enduring systemic change can only be achieved through a multi-pronged approach that combines monitoring and capacity-building activities, as well as collaborative action over the long term between different sets of stakeholders, and national governments play a critical role with respect to enacting and enforcing legislation that protects all workers’ rights.